Langkah sederhana menumbuhkan identitas nasional di lingkungan kampus - Dalailul Kafi, Ahmad An'im (Maliki Interdisciplinary Journal, 2025)
National identity is a crucial foundation for maintaining the unity and character of a nation, especially amid the growing wave of globalization. The campus environment, as a gathering place for the younger generation, holds a strategic role in shaping and instilling national values. This study aims to identify simple steps that students can take to foster national identity within the campus setting. The research method used is descriptive qualitative, with data collected through observation and literature study. The results show that activities such as using proper Indonesian language, participating in nationalism-themed events, appreciating local culture, and sharing positive nationalistic content on social media are effective and easy to implement. In conclusion, fostering national identity does not always require large and complex approaches but can begin with simple, consistent actions carried out by students in their daily campus life.